Project-Based Learning Through Herbal Product Development in the Phytochemistry Course for Vocational Pharmacy Students - Dwi Putri Rejeki; Safrijal Safrijal; Eva Novita (Jurnal Pendidikan Sains Indonesia, 2026)
Phytochemistry learning in vocational pharmacy education often poses challenges because students must understand abstract concepts, including secondary metabolites, phytochemical screening, extraction techniques, and herbal compound identification. Conventional lecture-centered learning also limits students’ opportunities to connect theoretical concepts with contextual pharmaceutical applications. Therefore, this study aimed to analyze the implementation of project-based learning (PjBL) through herbal product development in the phytochemistry course for vocational pharmacy students. This study employed a descriptive quantitative research design involving 29 vocational pharmacy students enrolled in the phytochemistry course during the 2025/2026 academic year. PjBL was implemented through contextual learning activities involving herbal material exploration, phytochemical discussions, collaborative investigations, and herbal product development. The research instruments included conceptual understanding tests adapted from the final semester examination, science process skills (SPS) observation sheets, and learning outcome documentation. Data were analyzed descriptively using mean scores, percentages, and achievement categories. The findings showed that PjBL positively contributed to students’ conceptual understanding and SPS The mean pretest score was 61.3, while the mean posttest score increased to 84.7. Most students also achieved satisfactory academic performance, with 75.9% obtaining grade A. In addition, students demonstrated positive achievement in collaboration, scientific communication, and observation skills. These findings indicate that PjBL can support meaningful, active, and contextual learning in vocational pharmacy education, particularly in phytochemistry courses